Changes in Markers of Thrombin Generation and IL-6 during Unicondylar Knee and Total Knee Arthroplasty - Su, Edwin P. (J Arthroplasty, 2017)
BACKGROUND: Total knee arthroplasty (TKA) is associated with a risk of thromboembolism requiring routine thromboprophylaxis, but there is debate about the risk with unicondylar knee arthroplasty (UKA) as it is believed to be a less invasive, more minor procedure with regard to surgical trauma. Because of this gap in knowledge, we sought to investigate the relative risk of thromboembolism with UKA compared to TKA and one-staged bilateral TKA (BTKA) by measuring the increase in circulating biochemical markers of coagulation at various time-points during the procedures. At the same time, we wanted to assess the relative degree of surgical trauma during the procedures by measuring IL-6, a marker of metabolic injury. METHODS: We prospectively studied a total of 75 patients: 25 patients undergoing UKA, unilateral TKA and BTKA respectively. All patients had neuraxial anesthesia, surgery performed with tourniquet and received no heparin or tranexamic acid (TXA). Radial artery blood samples were taken at four periods during surgery and assayed for circulating markers of thrombin generation: prothrombin fragment 1+2 (F1+2) and thrombin-antithrombin complexes (TAT); and a marker of metabolic injury, interleukin-6 (IL6), using ELISA assays. RESULTS: The circulating marker of thrombin generation, TAT, increased during all time-points (p<0.001) but was not significantly different between surgical treatment groups. F1+2 also rose significantly during surgery, with no significant difference between UKA and TKA. There was, however, a significant difference in F1+2 between BTKA and UKA or TKA (p<0.02). IL6 rose minimally with UKA but rose significantly with TKA and BTKA (p<0.001). CONCLUSION: Based on this data of circulating biochemical markers, patients undergoing UKA are at similar risk of thromboembolism with respect to TKA despite a lower index of metabolic injury. Therefore, we believe that UKA patients should receive thromboprophylaxis comparable to TKA patients. BTKA had the greatest increase in F1+2, a circulating marker of thrombogenesis; and IL6, a marker of metabolic injury.